Analisis Strategi DPMP4KB dalam Mengurangi Kasus Pernikahan Dini di Kota Magelang - Arya Wisnu Jati; Erni Saharuddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the strategies implemented by the Magelang City Department of Community Empowerment, Women, Child Protection, Population Control, and Family Planning (DPMP4KB) to reduce early marriage rates. The method used was descriptive qualitative, with data collection through observation, in-depth interviews, and documentation related to program and activity implementation. The results indicate that DPMP4KB still uses annual budget planning based on historical data, with an allocation of approximately Rp170 million for early marriage prevention through outreach and resource person involvement. However, the institution has begun implementing forecast-based planning through regular evaluations and community discussion forums, and adopting a bottom-up approach to make the program more relevant to local needs. Strategic management is carried out cyclically, involving field counselors who help adapt the program to social conditions in the community. These findings emphasize the need for a shift towards results-based planning, strengthening predictive data, and setting more measurable strategic targets. In this way, the implemented strategy will not only maintain institutional stability but also truly be able to address social challenges in a sustainable manner.